2007
DOI: 10.1080/00016480701230910
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the oral tongue in young patients: a matched-pair analysis

Abstract: Stage and treatment modality were similar in the two age groups. There were significant differences in overall survival (p=0.013) and disease-specific survival (p=0.046) favoring young patients. Rates of locoregional recurrence and distant metastasis were higher in the older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 23 publications
4
35
1
1
Order By: Relevance
“…Five of the 10 papers about the tumor-node-metastasis (TNM) Staging System indicated that a large amount of patients were diagnosed as T1 and/or T2 (8,(13)(14)(15)20) , being stages T3 and T4 (extensive tumors) predominant in other works (7,(10)(11)(12)18) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five of the 10 papers about the tumor-node-metastasis (TNM) Staging System indicated that a large amount of patients were diagnosed as T1 and/or T2 (8,(13)(14)(15)20) , being stages T3 and T4 (extensive tumors) predominant in other works (7,(10)(11)(12)18) .…”
Section: Resultsmentioning
confidence: 99%
“…As for sample size, the number of participants ranged from 10 to 2,223 young subjects, as described in Table 1. Age distribution of patients varied: individuals considered young were those aged 18-39 years (7,8,10,11) (23.5%), < 30 years (13,20) (3,6,8,9,(11)(12)(13)(14)(16)(17)(18)(19)(20)(21) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations